Nursing of a patient with acute mastitis and breast abscess treated by stone needle therapy combined with pricking and blood-letting therapy (砭石治疗联合刺络放血治疗1例急性乳腺炎脓肿形成期患者的护理) - CHEN Hong (陈宏); FAN Dongpan (范东盼); HE Jing (何静); (徐京巾); ZHANG Jing (张敬); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the effect observation and nursing management of a patient with acute mastitis and breast abscess treated by stone needle therapy combined with pricking and blood-letting therapy. Under the theory of Traditional Chinese Medicine syndrome differentiation, stone needle therapy combined with pricking and blood-letting therapy is able to alleviate pain and related symptoms caused by acute mastitis and breast abscess. (本文总结1例哺乳期急性乳腺炎脓肿形成期患者行砭石治疗联合刺络放血的效果观察及护理措施。在中医辨证施护理论指导下, 砭石治疗联合刺络放血治疗能有效缓解哺乳期急性乳腺炎患者疼痛, 改善临床症状。)